Does combiotic administration at artificial insemination improve fertility? - Duane L Davis; W E Scmidt; Jeffrey S Stevenson (Kansas Agricultural Experiment Station Research Reports, 1982)
Injecting gilts with 10 cc's combiotic at artificial insemination did not improve farrowing rate or litter size.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Artificial insemination; Fertility